Comparison of incidence, rate and length of all-cause hospital admissions between adults with normoglycaemia, impaired fasting glucose and diabetes: a retrospective cohort study in Geelong, Australia. Issue 3 (23rd March 2018) - Sajjad, Muhammad Amber; Holloway, Kara L; de Abreu, Lelia L F; Mohebbi, Mohammadreza; Kotowicz, Mark A; Pedler, Daryl; Pasco, Julie A
Abstract : Objective: To determine whether adults with normoglycaemia, impaired fasting glucose (IFG) and diabetes differed according to the incidence, rate, length and primary reasons for hospital admission. Design: Retrospective cohort study. Setting: Barwon Statistical Division, Geelong, Australia. Participants: Cohort included 971 men and 924 women, aged 20+ years, participating in the Geelong Osteoporosis Study. Glycaemic status was assessed at cohort entry using fasting plasma glucose, use of antihyperglycaemic medication and/or self-report. Primary and secondary outcome measures: Primary outcome measure was any admission to the major tertiary public hospital in the study region over the follow-up period. Secondary outcome measures were admission rate and length (days). Results: Over a median follow-up of 7.4 years (IQR 5.3–9.6), participants with diabetes, compared with those with normoglycaemia, were two times as likely to be hospitalised (OR 2.07, 95% CI 1.42 to 3.02), had a higher admission rate (incidence rate ratio 1.61, 95% CI 1.17 to 2.23) and longer hospital stay (third quartile difference 7.7, 95% CI 1.3 to 14.1 and ninth decile difference 16.2, 95% CI 4.2 to 28.3). IFG group was similar to normoglycaemia for the incidence, rate and length of admission. Cardiovascular disease-related diagnoses were the most common primary reasons for hospitalisation across all glycaemic categories. Conclusions: Our results show increased incidence, rate and length of all-cause hospital admission in adults with diabetes as compared with normoglycaemia; however, we did not detect any associations for IFG. Interventions should focus on preventing IFG-to-diabetes progression and reducing cardiovascular risk in IFG and diabetes.